Pseudoxanthoma elasticum overlaps hereditary spastic paraplegia type 56. (31st March 2021) - Legrand, A.; Pujol, C.; Durand, C. M.; Mesnil, A.; Rubera, I.; Duranton, C.; Zuily, S.; Sousa, A. B.; Renaud, M.; Boucher, J. L.; Pietrancosta, N.; Adham, S.; et al.
Abstract: Purpose: Pseudoxanthoma elasticum (PXE) is a recessive disorder involving skin, eyes and arteries, mainly caused by ABCC6 pathogenic variants. However, almost one fifth of patients remain genetically unsolved despite extensive genetic screening of ABCC6, as illustrated in a large French PXE series of 220 cases. We searched for new PXE gene(s) to solve the ABCC6 ‐negative patients. Methods: First, family‐based exome sequencing was performed, in one ABCC6‐ negative PXE patient with additional neurological features, and her relatives. CYP2U1, involved in hereditary spastic paraplegia type 56 (SPG56), was selected based on this complex phenotype, and the presence of two candidate variants. Second, CYP2U1 sequencing was performed in a retrospective series of 46 additional ABCC6 ‐negative PXE probands. Third, six additional SPG56 patients were evaluated for PXE skin and eye phenotype. Additionally, plasma pyrophosphate dosage and functional analyses were performed in some of these patients. Results: 6.4% of ABCC6 ‐negative PXE patients ( n  = 3) harboured biallelic pathogenic variants in CYP2U1 . PXE skin lesions with histological confirmation, eye lesions including maculopathy or angioid streaks, and various neurological symptoms were present. CYP2U1 missense variants were confirmed to impair protein function. Plasma pyrophosphate levels were normal. Two SPG56 patients (33%) presented some phenotypic overlap with PXE. Conclusion: CYP2U1 pathogenic variants are found in unsolved PXE patients with neurological findings, including spastic paraplegia, expanding the SPG56 phenotype and highlighting its overlap with PXE. The pathophysiology of ABCC6 and CYP2U1 should be explored to explain their respective role and potential interaction in ectopic mineralization. Abstract :